The prominent role of agricultural advisory services on cocoa agribusiness development in Aceh, Indonesia - Elvira Iskandar; Siti Amanah; Aida Vitayala S. Hubeis; Dwi Sadono (Jurnal Penyuluhan, 2020)
This paper aims to analyze the cocoa extension system and factors influencing agribusiness performance on cocoa production. Research was conducted in Pidie Jaya and Southeast Aceh District in July – October 2019. Data and information were gathered from 10 extension workers and 352 cocoa farmers by survey methods. The research result showed that cocoa extension system in Aceh consist of subsystem innovation policy, generating subsystem, delivery subsystem and receiving subsystem. The public extension services have reached 84.66% farmers and private extension services have facilitated 75.85% farmers, and only 11.93% farmers by farmer's leaders. There were a significant correlation between supporting advisory services with the cocoa agribusiness performance. The role of local community has a strong influence in disseminating and implementing technology on cocoa agribusiness. There are different issues need to solve cocoa agribusiness managed by small-scale farmers are price incentive policies, supporting fermentation and marketing units of cocoa beans, stimulating the establishment of cocoa processing industry and increasing the quality of advisory services. Keywords: agribusiness performance, cocoa farming, extension system